انتشار الطفيليات في منطقة الساحل السوري - دغمان, دعد (Latakia University Journal -Medical Sciences Series, 2019)
تنتشر الطفيليات عبر العالم، ويعاني منها أكثر 25% من سكان العالم. ويختلف مدى هذا الانتشار من منطقة لأخرى تبعاً لعوامل صحية، اقتصادية، اجتماعية، وبيئية وكذلك الأمر ضمن البلد الواحد. هدف هذا البحث هو معرفة مدى انتشار الطفيليات في منطقة الساحل السوري ومعرفة الفرق في هذا الانتشار مابين مدينة اللاذقية ومنطقة الريف المحيط بها. شمل البحث 360 مريضاً من مراجعي العيادة الهضمية، بلغت نسبة التطفل الإجمالي 38.6% وكانت النسبة الأعلى في الريف إذ وصلت حتى 41.7% بينما كانت في مدينة اللاذقية 34.1% وعلى الرغم من ارتفاع نسبة التطفل هذه إلا أنها تبقى الأقل ضمن القطر بالمقارنة مع الدراسات السورية السابقة. Parasites prevail around the globe; more than 25% of the world population suffer from it. The prevalence of parasites differs from one region to another, according to many factors such as economical, sanitary, social, and environmental; they also differ within the same country. This study aims to determine the prevalence of parasites on the Syrian coast and define the difference in this prevalence between the city of Lattakia and the countryside surrounding it. This study includes 360 patients (out- patients). The total percentage of the positive cases is 38.6%; the higher percentage of 41.7% is in the countryside, while it is 34.1% in the city of Lattakia. In spite of this high percentage of the positive cases, but it is still the lowest one in the country compared to previous Syrian studies.